Parental mediation in the age of mobile technology - Nagy, Beáta; Kutrovátz, Kitti; Király, Gábor; Rakovics, Márton (Children & society, 2023)
This paper explores the impacts of adolescents' screen time, learning outcomes and parental performance in relation to different mediation strategies. These issues are addressed through the analysis of a representative survey carried out with 1000 families in Hungary in 2017. Within this research, 12–16‐year‐old teenagers and their parents were asked about their experiences and perceptions of mediation. Four main parental strategies can be identified: balancing mediation, restriction, permission and ad hoc mediation. The significance of parental performance in the analyses indicates that parental mediation forms part of the contemporary parenting skillset and correlates with perceptions of children's screen time and subjective quality of parenting.